Homer, Humanism, Holocaust - Goldwyn, Adam J. author. aut Link
XI, 150 p.
Keywords: This book examines how Jewish intellectuals during and after the Second World War reinterpreted Homer’s epics, the Iliad and the Odyssey, in light of their own wartime experiences, drawing a parallel between the ancient Greek genocide of the Trojans and the Nazi genocide of the Jews. The wartime writings of Theodore Adorno, Hannah Arendt, Erich Auerbach, Rachel Bespaloff, Hermann Broch, Max Horkheimer, Primo Levi, and others were attempts both to understand the collapse of European civilization and the Enlightenment through critiques of their foundational texts and to imagine the place of the Homeric epics in a new post-War humanism. The book thus also explores the reception of these writers, analyzing how Jewish child-survivors like Geoffrey Hartman and Hélène Cixous and writers of the post-Holocaust generation like Daniel Mendelsohn continued to read the epics as narratives of grief, trauma, and woundedness into the twenty-first century. Adam J. Goldwyn is Associate Professor of English at North Dakota State University, USA. He is the author of Byzantine Ecocriticism: Women, Nature, and Power in the Medieval Greek Romance (Palgrave Macmillan, 2018) and Witness Literature in Byzantium: Narrating Slaves, Prisoners, and Refugees (Palgrave Macmillan, 2021), and co-editor of Mediterranean Modernism: Intercultural Exchange and Aesthetic Development (Palgrave Macmillan, 2016). .